Formation of nitric oxide dimers on MgO-supported gold particles - Fuente, Silvia Andrea (2012)
We present density functional theory (DFT) calculations on the formation of nitric oxide dimers (N 2O 2) on Au atoms, dimers and trimers adsorbed on regular O 2 - sites and neutral oxygen vacancies (F s sites) of the MgO(100) surface. The study of the N 2O 2 species is of great interest since it has been detected in the NO reduction reaction as an intermediate towards the formation of N 2O. We found that the coupling of a NO molecule with a previously adsorbed one on Au/MgO is energetically favorable on Au 1 and Au 3, but unfavorable on Au 2. The stability of N 2O 2 is in direct relation with the amount of charge taken from the support. Furthermore, one of the N - O bonds can be activated as a result of the attraction between the negatively charged NO dimer and the ionic oxide surface. In fact, for Au 1 anchored on the F s site a barrierless reaction occurs between N 2O 2 and a third NO molecule, forming adsorbed N 2O and NO 2. © 2012 Elsevier B.V. All rights reserved.